Distributions of cadmium, zinc, and polyphenols in Gamblea innovans. Issue 3 (23rd February 2019) - Sakurai, Misuzu; Tomioka, Rie; Hokura, Akiko; Terada, Yasuko; Takenaka, Chisato
Abstract: Gamblea innovans is a Cd- and Zn-accumulating deciduous tree widely distributed in the secondary forests of Japan. We aimed to understand the characteristics of Cd and Zn accumulation in G. innovans in order to effectively utilize the species for phytoremediation. To accomplish that, we studied the relationship between secondary metabolite concentrations and the accumulation and distributions of Cd and Zn in G. innovans leaves and basal stems using micro-X ray fluorescence (µ-XRF). Our results showed a negative correlation between Zn leaf concentrations and polyphenol/2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity. This finding might be related to stress or the manifestation of a mechanism for tolerance to Cd and Zn accumulation. In addition, we observed that Cd accumulated primarily in the apoplastic region of surface tissues such as bark and the epidermis of leaves, whereas Zn accumulated in both apoplastic and symplastic regions. Thus, it might be possible that G. innovans can distinguish between Cd and Zn and control their translocation.